Legal Deliberation and Police Reform to Increase Transparency and Accountability in Law Enforcement - Dwi Asmoro; Riswadi Riswadi (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
The research method used is normative juridical research that will be used to analyze the concepts of legal deliberation and police reform from a legal perspective that involves an in-depth understanding of the legal framework governing law enforcement and the role of the police, as well as an assessment of the extent to which the principles of legal deliberation can be implemented in the legal context. Legal deliberation focused on police reform is an important step in increasing transparency and accountability in law enforcement. By encouraging inclusive dialogue and active participation of various stakeholders, including civil society and watchdog institutions, this deliberative process can strengthen the integrity and effectiveness of the police institution. Through policy review, training, and rigorous oversight, police reform can result in a more transparent, accountable, and community service-oriented system, which in turn will increase public trust and fairness in law enforcement.